Quantification of the Dental Morphology of Orangutans - P. Nambiar; J. John; Samah M. Al-Amery; K. Purmal; W. L. Chai; W. C. Ngeow; N. H. Mohamed; S. Vellayan (The Scientific World Journal)
Orangutans are believed to have close biological affinities to humans. Teeth being the hardest tissue provide useful information on primate evolution. Furthermore, knowledge of the pulp chamber and root canal morphology is important for dental treatment. A female Bornean orangutan and a Sumatran male orangutan skull were available for this study. Both of their dentitions, comprising 50 teeth, were scanned employing the cone-beam computed tomography for both metrical and nonmetrical analyses. Measurements included tooth and crown length, root length, enamel covered crown height, root canal length (posterior teeth), length of pulpal space (anterior teeth), and root canal width. Nonmetrical parameters included number of canals per root, number of foramina in each root, and root canal morphology according to Vertucci’s classification. It was found that the enamel covered crown height was the longest in the upper central incisors although the canine was the longest amongst the anterior teeth. Both the upper premolars were three-rooted while the lower second premolar of the Sumatran orangutan was two-rooted, with two foramina. The mandibular lateral incisors of the Bornean orangutan were longer than the central incisors, a feature similar to humans. In addition, secondary dentine deposition was noticed, a feature consistent with aged humans.